2007
DOI: 10.1039/b511238a
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavonoids of the Leguminosae

Abstract: Isoflavonoids are found predominantly in subfamily Papilionoideae of the Leguminosae. This review describes more than 420 new examples of Leguminosae isoflavonoids, giving details of their source, identification, biological activity, synthesis, and ecological or chemosystematic significance. Other topics addressed include the application of hyphenated analytical techniques to the characterisation of legume-derived isoflavonoids, and advances made in biosynthetic studies. A checklist of new compounds by species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
96
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(103 citation statements)
references
References 332 publications
(411 reference statements)
1
96
0
3
Order By: Relevance
“…These compounds also co-occur in E. abyssinca [5], supporting the biogenetic relationship between arylbenzofurans and isoflav-3-enes. The arylbenzofuran burttinol D co-occurs with the isoflav-3-ene burttinol A in the roots of E. burttii [12], and similar biogenetic relationship has been suggested for these compounds [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds also co-occur in E. abyssinca [5], supporting the biogenetic relationship between arylbenzofurans and isoflav-3-enes. The arylbenzofuran burttinol D co-occurs with the isoflav-3-ene burttinol A in the roots of E. burttii [12], and similar biogenetic relationship has been suggested for these compounds [11].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that this compound co-occurs in E. varigata with the isoflav-3-ene eryvarin H (3) which has identical oxygenation pattern as compound 2 [10]. It has been proposed that eryvarin L is derived from eryvarin H in this plant [11]. These compounds also co-occur in E. abyssinca [5], supporting the biogenetic relationship between arylbenzofurans and isoflav-3-enes.…”
Section: Resultsmentioning
confidence: 99%
“…However, a literature search showed that the geometry of the B/C-ring junction of 12a-hydroxyrotenoids could be assigned by analysis of their chemical shift value of H-1 in their 1 H-NMR spectra as well as the comparison of their optical rotation value with those of known compounds. Literature revealed that the chemical shift value of H-1 would be δ H 6.6-7.0 for a cis-junction as in 4′,5′-dihydro-11,5′-dihydroxy-4′-methoxytephrosin, 20) or in (6aα,12aα)-12a-hydroxyelliptone, 21) and around δ H 8.0 for a trans-junction as in boeravinone C. 13) Further it has been observed that natural trans-junction 12a-hydroxyrotenoids would be either 6aα,12aβ-configuration as in coccineone E 19) and abronione 22) or 6aβ,12aα-configuration as in (+)-12a-epimilletosin 23) and usararotenoid C. 24) Those with a 6aα,12aβ-configuration display negative specific rotation, 13,19,22) while those with a 6aβ,12aα-configuration display positive specific rotation. 23,24) The chemical shift value for H-1 (δ H 8.33) of 3 is strongly deshielded when compared to the value observed for rotenoids with cis-B/C ring junction indicating that the B/C ring junction in 3 has a trans-geometry.…”
Section: Resultsmentioning
confidence: 99%
“…Literature revealed that the chemical shift value of H-1 would be δ H 6.6-7.0 for a cis-junction as in 4′,5′-dihydro-11,5′-dihydroxy-4′-methoxytephrosin, 20) or in (6aα,12aα)-12a-hydroxyelliptone, 21) and around δ H 8.0 for a trans-junction as in boeravinone C. 13) Further it has been observed that natural trans-junction 12a-hydroxyrotenoids would be either 6aα,12aβ-configuration as in coccineone E 19) and abronione 22) or 6aβ,12aα-configuration as in (+)-12a-epimilletosin 23) and usararotenoid C. 24) Those with a 6aα,12aβ-configuration display negative specific rotation, 13,19,22) while those with a 6aβ,12aα-configuration display positive specific rotation. 23,24) The chemical shift value for H-1 (δ H 8.33) of 3 is strongly deshielded when compared to the value observed for rotenoids with cis-B/C ring junction indicating that the B/C ring junction in 3 has a trans-geometry. It exhibited negative optical rotation, therefore, from biogenetic considerations of 12a-hydroxyrotenoids of the family Nyctaginaceae, 13,19,22) the absolute configurations at C-6a and C-12a in 3 are likely to be as in boeravinone C, coccineone E and other related natural rotenoids.…”
Section: Resultsmentioning
confidence: 99%
“…Isoflavones are found almost exclusively in legumes and have several different biological activities (Veitch, 2007). In legumes, isoflavones mediate plant-microbe interaction, induce Nod gene of nitrogen fixing bacteria.…”
Section: Biological Roles Of Isoflavones In Plantsmentioning
confidence: 99%